The little French bridal shop - Dupee, Jennifer (St. Martin's Press, 2021)
Renovating an inherited colonial property in her Massachusetts hometown to manage painful losses, Larissa buys a wedding gown as a private joke only to have word of her impending nuptials spread throughout the community.